CarbonXS GUI: a graphical front‐end for CarbonXS. Issue 6 (14th November 2017) - Tsui, Lok-kun; Garzon, Fernando
Abstract : CarbonXS GUI is a graphical user interface to CarbonXS . It is used to fit the X‐ray diffraction patterns of disordered and graphitized carbon materials to extract structural parameters such as coherence size and strain. Abstract : The crystallographic structure of disordered carbons impacts their performance in components for fuel cells, batteries and catalyst supports. Obtaining parameters such as lattice constants and crystal domain size requires an appropriate model for these carbons, a task accomplished with the Fortran program CarbonXS published in 1993. CarbonXS GUI contains an updated version of CarbonXS and a graphical user interface wrapper. This new version provides a graphical method of configuring and operating CarbonXS, a calculation mode to simulate diffraction patterns, and immediate feedback in the form of fit–source and difference plots. CarbonXS GUI is available for free on Windows, Linux and Mac OSX athttp://github.com/lktsui/carbon_xs_gui .